Antibiotic Prophylaxis for Open Chest Management After Pediatric Cardiac Surgery. Issue 9 (September 2019) - Hatachi, Takeshi; Sofue, Toshiki; Ito, Yukie; Inata, Yu; Shimizu, Yoshiyuki; Hasegawa, Moyu; Kugo, Yosuke; Yamauchi, Sanae; Iwai, Shigemitsu; Takeuchi, Muneyuki
Abstract : Objectives: Although open chest management optimizes hemodynamics after cardiac surgery, it increases postoperative infections and leads to increased mortality. Despite the importance of antibiotic prophylaxis during open chest management, no specific recommendations exist. We aimed to compare the occurrence rates of bloodstream infection and surgical site infection between the different prophylactic antibiotic regimens for open chest management after pediatric cardiac surgery. Design: Retrospective, single-center, observational study. Setting: PICU at a tertiary children's hospital. Patients: Consecutive patients younger than or equal to 18 years old with open chest management after cardiac surgery followed by delayed sternal closure, between January 2012 and June 2018. Interventions: None. Measurements and Main Results: We compared the composite occurrence rate of postoperative bloodstream infection and surgical site infection within 30 days after cardiac surgery between three prophylactic antibiotic regimens: 1) cefazolin, 2) cefazolin + vancomycin, and 3) vancomycin + meropenem. In 63 pediatric cardiac surgeries with open chest management, 17 bloodstream infections, and 12 surgical site infections were identified postoperatively. The composite occurrence rates of bloodstream infection and surgical site infection were 10 of 15 (67%), 10 of 19 (53%), and nine of 29 (31%) in the cefazolin, cefazolin + vancomycin, and vancomycin + meropenem regimens, respectively ( p = 0.07). After adjusting for age, open chest management duration, extracorporeal membrane oxygenation use, and nasal methicillin-resistant Staphylococcus aureus colonization in multivariable analysis, there was no significant difference between the cefazolin and the cefazolin + vancomycin regimens ( p = 0.19), while the vancomycin + meropenem regimen had a lower occurrence rate of bloodstream infection and surgical site infection than the cefazolin regimen (odds ratio, 0.0885; 95% CI, 0.0176–0.446; p = 0.003). Conclusions: In this study, a lower occurrence rate of postoperative bloodstream infection and surgical site infection was observed among patients with broad-spectrum antibiotic regimen after pediatric cardiac surgery with open chest management. Further studies, ideally randomized controlled studies investigating the efficacy of broad-spectrum antibiotics and their complications, are warranted before routine implementation of broad-spectrum prophylactic antibiotic regimen.